Railways in Lithuania: from Tsarist Russia to Rail Baltica - Maskeliūnaitė, Lijana (Transport, 2021)
Lithuania is a transit country. It is a small but significant territory between East and West. This fact is substantiated by the history of the country railways, which started when Tsarist Russia launched the construction of the railway between Saint-Petersburg and Warsaw. There is not much research into the history of railways in Russia, also in Lithuania. Besides, not all available information is reliable due to the nihilistic attitudes towards Tsarism of that time. Only some of the railways in the former Soviet Union were written and talked about. The history of the Lithuania railway is not an exception. Different written sources provide a variety of dates for the first railway to be built in Lithuania. They mirror varied events in the history of Lithuanian railways, thus all of them must be taken into consideration. The article presents the evolution of Lithuanian railway transport from Tsarist Russia to Rail Baltica, which is the European railway project currently implemented in Lithuania. The article discusses the world’s first railways including the ones in Tsarist Russia when the history of Lithuanian railways started. The article also considers the building of the first railway in Lithuania, construction of railway stations, setting the transportation tariffs, selection of railway employees. The author of the article employs historical and online resources as well as a long-standing personal experience in railway transport. The research into Tsar Family’s diaries and historical novels makes it possible to disclose the facts that are not widely known. The author considers the future of Lithuania with reference to the construction of the European railway Rail Baltica. The article would be useful for the readers who are interested in the historical development and future of Lithuanian railways.